Technological innovation and SME performance: Mediating roles of digital transformation & resource integration, moderating roles of strategic orientation & market dynamics - Pan, Jingchao; Ahmad, Noor Hazlina (International Journal of Management and Sustainability, 2025)
This study aims to investigate the impact of technological innovation (TI) on the performance of small and medium-sized enterprises (SMEs), while exploring the mediating roles of digital transformation (DT) and resource integration (RI), and the moderating effects of strategic orientation (SO) and market dynamics (MD). A quantitative research design was adopted using a structured questionnaire distributed to employees working in various Chinese companies. The population consisted of full-time employees across diverse industries in urban China. A sample of 412 respondents was selected using stratified random sampling to ensure representation across sectors. A structured questionnaire was administered to key managerial respondents, and the data were analyzed using SmartPLS structural equation modeling (SEM). Measurement scales were adapted from established studies to ensure validity and reliability of constructs. The results confirmed that TI has a significant positive impact on SME performance. Additionally, DT and RI were found to mediate this relationship effectively. The moderating analyses revealed that SO and MD significantly strengthen the positive effect of TI on performance, underscoring the importance of internal strategic alignment and responsiveness to external environments. This study advances the literature by integrating Resource-Based View (RBV) and Dynamic Capabilities Theory (DCT) to explain how SMEs can leverage innovation for superior outcomes. Beyond theoretical contributions, the findings provide practical guidance for SME managers and policymakers on embedding innovation strategies, fostering digital transformation, and aligning resources to enhance sustainability and long-term growth in volatile markets.